Pengaruh Profitabilitas, Board Gender, Dan Likuiditas Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Moderasi (Studi Empiris Pada Perusahaan Manufaktur Yang Bergerak Dibidang Consumer Goods Yang Terdaftar Di Bei Periode 2011-2016) - Elisabeth Octavia Kamal dan Indra Widjaja (Universitas Tarumanagara, 2019)
The purpose of this paper, is to analyze the influence of Profitability, Board Gender, and Liquidity toward Firm Value with Dividend Policy as moderating variable. The sample collection technique has been done by using purposive sampling method, and the samples are 12 companies. The statistic test method has been done by using multiple linier regression analysis and moderated regression analysis. The independent variables in this research are profitability which proxied with return on equity and net profit margin, board gender, and liquidity which proxied with current ratio and quick ratio. The dependent variable is firm value which proxied with price to book value. The moderating variable is dividend policy which proxied with dividend payout ratio. The result of this research show that (1) profitability, board gender, and liquidity simultaneously have significant effect towards firm value, (2) profitability, board gender, and liquidity with dividend policy as moderating variable simultaneously have significant effect towards firm value. According to the result of partial coefficient determination (t-test), return on equity and board gender have a positive significant effect towards firm value. Net profit margin has negative significant effect towards firm value. Current ratio has positive insignificant effect towards firm value, while quick ratio has a negative insignificant effect towards firm value. According to the result of moderated regression analysis, dividend policy as moderating variable is able to moderate the effect of profitability towards firm value but is not able to moderate the effect of board gender and liquidity towards firm value.